Penerapan Metode TOPSIS Dalam Pemilihan Lokasi Usaha Strategis - Raditya Rimbawan Oprasto (Journal of Data Science and Information Systems, 2023)
This study aims to provide recommendations for strategic business places for business actors using criteria of building area, rental prices, road access, and distance from the center of the crowd. So that the results of business place recommendations in supporting business actors in determining strategic business locations. TOPSIS is a method in multi-criteria decision making that selects the best alternative based on the distance of positive and negative ideal solutions from the criteria used in determining alternatives. Based on the results of the ranking of strategic business location selection that gets rank 1, namely Location 3 with a value of 0.633992256, rank 2 is Location 1 with a value of 0.572951301, rank 3 is Location 4 with a value of 0.5, rank 4 is Location 2 with a value of 0.366023913.